TESOL Methodology: Teaching English as a Second or Other Language - yolanda, alvina; purwaningsih, dewi ismu (English Literature Department, Adab and Humanities Faculty, 2020)
Approaches of language teaching and learning have always been created and developed over the time. This change could not be separated with the influence of both Second Language Acquisition (SLA) and pedagogical theories in ELT. Learner centre, a present day approach which is likely aligned with those theories, has become a key concept with regards to how languages are learned and taught despite some of the barriers of its implementation. Learner-centre is a perspective which focuses on the learners’ experiences, perspectives, backgrounds, talents, interests, capacities, and needs. Learner centre may offers benefits for promoting effective process of learning. It enables learners’ cognitive process to be well-developed.